Disseminated Mycobacterium intracellulare Infection in an Immunocompetent Host - Kim, Won-Young (The Korean Academy of Tuberculosis and Respiratory Diseases, 2012)
Disseminated Mycobacterium avium complex (MAC) infection can occur in immunocompromised patients, and rarely in immunocompetent subjects. Due to the extensive distribution of the disease, clinical presentation of disseminated MAC may mimic malignancies, and thorough examinations are required in order to make accurate diagnosis. We report a case of disseminated Mycobacterium intracellulare disease in an immunocompetent patient, which involved the lung, lymph nodes, spleen, and multiple bones. F-18 fluorodeoxyglucose positron-emission tomography imaging showed multiple hypermetabolic lesions, which are suggestive of typical hematogenous metastasis. However, there was no evidence of malignancy in serial biopsies, and M. intracellulare was repeatedly cultured from respiratory specimens and bones. Herein, we should know that disseminated infection can occur in the immunocompetent subjects, and it can mimic malignancies.